Strengthening Economic Ties Amidst the Maritime Dispute Between the Philippines and China - Aquino, Perfecto G.; Bao, Tran Thai; Jalagat, Revenio; Thao, Nguyen Thi Phuong; Hiep, Duong Quang (Universiti Utara Malaysia Press, 2023)
The Sino-Philippines relations underwent many challenges and changes for over two decades. It is characterized as a “fighting and cooperating” relationship in various domains, specifically in the context of their long-standing dispute over the South China Sea (SCS). The two countries have established diplomatic ties since 1975, and although the relationship between the Philippines and China has gone a long way in forging economic relations with regard to conducting a more conducive, progressive, and fair-trade partnership, China is still perceived as a significant threat to the national security of the Philippines. The Philippine government has lodged numerous complaints with international bodies about China’s violation of the law of the sea, particularly the UNCLOS. However, the regional environment and China’s phenomenal rise in becoming an economic super power, and in particular the positive outcome resulting from the establishment of the ASEAN Economic Community (AEC), have all aided in developing the economic cooperation between the Philippines and China. Against the backdrop of these developments, the present article has focused on analyzing the two countries’ relations in terms of the financial impacts from the surging waves of disagreements over the two countries’ maritime belt areas in the South China Sea. It is also an empirical review of the literature on the myriad recommendations of international organizations, international courts, experts, jurists, and researchers, which seek to find solutions by providing legal viewpoints and political opinions on the issue of the maritime conflict between the Philippines and China. These are ongoing attempts for a peaceful solution to the maritime disputes between the two countries, as well as for the benefit of the rest of the ASEAN member nations.